Yritysten kriisinkestävyys ja siihen liittyvät tekijät - Jyrki Ali-Yrkkö; Natalia Kuosmanen; Mika Pajarinen; Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2024)
– This report examines the resilience of firms during crises from two perspectives: their ability to resist crises and their capacity to recover. The findings reveal that innovative firms are less likely to cease operations than other firms and are more likely to recover faster. The study further supports the notion that a high level of solvency and a strong ability to make interest payments (interest coverage ratio) reduce the risk of a firm exiting the market or experiencing an exceptionally large decline in revenue.
Keywords: F14; L08; 330; Resilience; Crisis; Firms